Advances in Remote Sensing in Coastal Geomorphology ? (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
For the geomorphological study of the coast, there is now a great number of available methods for remote detection, including satellite images or aerial photogrammetry, as well as other methods closer to land, in which geodesic–topographic, on-land photogrammetry, UAV, lidar, and TLS techniques are utilized. Depending on the methodology, precisions can vary from metric to millimetric. Studies in emerging sectors are often linked to underwater dynamics, sedimentation, and morphology.